Veiksmažodžio versti leksinė semantinė struktūra - Pakerys, Jurgis (Kalbotyra, 1997)
This article presents an analysis of the polysemantic Lithuanian verb versti. So far research has revolved around the non-prefixed and non-reflexive forms of the said verb. The analysis is based on the methods of onomasiological explanation, syntactical, logical-semantical, and lexical valence analysis. By way of conclusion, the meanings of versti are classified and arranged in a hierarchical system and the matrix of semantical components is provided.